Population genomic structure and adaptation in the zoonotic malaria parasite Plasmodium knowlesi - Assefa, S.; Lim, C.; Preston, M.D.; Duffy, C.W.; Nair, M.B.; Adroub, S.A.; Kadir, K.A.; Goldberg, J.M.; Neafsey, D.E.; Divis, Paul Cliff Simon; Clark, T.G.; Duraisingh, M.T.; et al. (Proceedings of the National Academy, 2015)
Malaria cases due to the zoonotic parasite P. knowlesi are being increasingly reported throughout Southeast Asia and in travelers returning from the region. To test for evidence of signatures of selection or unusual population structure in this parasite, we surveyed genome sequence diversity in 48 clinical isolates recently sampled from Malaysian Borneo and 5 lines maintained in laboratory rhesus macaques after isolation in the 1960s from Peninsular Malaysia and the Philippines. Overall genome-wide nucleotide diversity (π = 6.03 x 10-3) was much higher than has been seen in worldwide samples of either of the major endemic malaria parasite species P. falciparum and P. vivax. A remarkable substructure is revealed within P. knowlesi, consisting of two major sympatric clusters of the clinical isolates, and a third cluster comprising the laboratory isolates. There was deep differentiation between the two clusters of clinical isolates (mean genome-wide FST = 0.21, with 9,293 SNPs having fixed differences of FST = 1.0). This showed marked heterogeneity across the genome, mean FST values of different chromosomes ranging from 0.08 to 0.34, with further significant variation across regions within several chromosomes. Analysis of the largest cluster (Cluster 1, 38 isolates) indicated long-term population growth, with negatively skewed allele frequency distributions (genome-wide average Tajima’s D = -1.35). Against this background there was evidence of balancing selection on particular genes, including the circumsporozoite protein (csp gene had the top value of Tajima’s D = 1.57), and scans of haplotype homozygosity implicate several genomic regions to be under recent positive selection.